Permasalahan Tanpa Solusi Tentang Buruknya Pengawasan Ketenagakerjaan Di Indonesia - Dewi, Ratna; Tampubolon, Jeklira (Jurnal Global Ilmiah, 2025)
Labor inspection in Indonesia continues to face structural challenges that undermine its effectiveness. The insufficient number of labor inspectors compared to the number of enterprises, regulatory inconsistencies, lack of independence, limited funding, and corruption are the primary factors weakening the supervision function. As a result, violations of labor standards and occupational safety (K3) frequently occur. This article analyzes the root causes of weak labor inspection based on Soerjono Soekanto's theory of legal effectiveness and evaluates government responses, including the establishment of Labor Norm Cadres (KNK), the implementation of the Labor Compliance Program (PROKEP), and the digitization of inspection systems. While some improvements have been made, labor inspection in Indonesia remains suboptimal and requires more comprehensive reforms.